Cross-border trade secret disputes in the European Union : jurisdiction and applicable law - Lundstedt, Lydia (Elgar monographs in private international law, 2023)
"In today's data-driven economy, it is essential for companies to protect their trade secrets against unlawful acquisition,use and disclosure; with the ease of digital communications, employee migration and international trade, trade secret violations now often occur across national borders. This book examines how trade secret protection can differ across jurisdictions, where trade secret holders can bring proceedings, and which country's law is applicable. Lundstedt provides a European perspective, analysing how the EU's rules on jurisdiction and applicable law relate to the EU's wider objectives on encouraging cross-border innovation activities. Using common trade secret scenarios as a springboard for analysis, this book questions whether EU private international law rules can be interpreted to facilitate the objectives of the EU Trade Secret Directive and in doing so it sets out a detailed examination of both regimes. Providing a clear and comprehensive perspective on a complex area of law, this book will be valuable for scholars of private international law, intellectual property law and EU law. Due to its practical approach to analysis, it will also be useful for policy makers and legal practitioners seeking information about uncertainties that exist in the current law"--